Literatur Riview Jurnal Uji Antioksidan Tanaman Jamblang (Syzygium Cumini L.) Menggunakan Metode Dpph Dengan Spektrofotometer Uv-Vis - Ermi Abriyani; Nurhadi Amirulloh; Lutfia Ulfiani; Annis Fathurrohmah; Anjar Rismawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Jamblang (Syzygium cumini) is one of Indonesia's local fruits. All parts of this plant can be used for treatment, one of which is as an antioxidant. The genus Syzygium family myrtaceae is one of the largest genera in Indonesia, including species originating from guava, one of which is the jamblang plant (Syzygium cumini) which has natural antioxidant activity. The aim of this literature review is to provide an overview of the literature review of Syzygium Cumini L. until 2022. This article also intends to review advances in the botanical, phytochemical, and pharmacological studies of Syzygium Cumini L, which will provide useful information for further investigation and application. Syzygium Squid L in medicine and food